Albumin uptake in human podocytes: a possible role for the cubilin-amnionless (CUBAM) complex. Issue 1 (December 2017) - Gianesello, Lisa; Priante, Giovanna; Ceol, Monica; Radu, Claudia; Saleem, Moin; Simioni, Paolo; Terrin, Liliana; Anglani, Franca; Del Prete, Dorella
Abstract Albumin re-uptake is a receptor-mediated pathway located in renal proximal tubuli. There is increasing evidence of glomerular protein handling by podocytes, but little is known about the mechanism behind this process. In this study, we found that human podocytesin vitro are committed to internalizing albumin through a receptor-mediated mechanism even after exposure to low doses of albumin. We show that these cells express cubilin, megalin, ClC-5, amnionless and Dab2, which are partners in the tubular machinery. Exposing human podocytes to albumin overload prompted an increase inCUBILIN, AMNIONLESS andCLCN5 gene expression. Inhibiting cubilin led to a reduction in albumin uptake, highlighting its importance in this mechanism. We demonstrated that human podocytes are committed to performing endocytosisvia a receptor-mediated mechanism even in the presence of low doses of albumin. We also disclosed that protein overload first acts on the expression of the cubilin-amnionless (CUBAM) complex in these cells, then involves the ClC-5 channel, providing the first evidence for a possible role of the CUBAM complex in albumin endocytosis in human podocytes.